From forest to farmland: palaeoecological and geospatial reconstruction of land-use change in the Lake Simcoe watershed, Ontario - Edmunds, Lily (My University, 2026)
Reconstructing long-term land-use change and its ecological consequences requires integrating archaeological, historical, and palaeoecological evidence across spatial and temporal scales. This thesis applies a nested palaeoecological and historical aerial photo and GIS-based framework to the Lake Simcoe watershed (southern Ontario, Canada), combining a continuous Holocene sediment record from Bass Lake (Langman) with high-resolution twentieth-century records from three hydrologically open wetlands spanning an urban–rural gradient (Beaver River, Rogers Reservoir, and Baileys Ecopark). Pollen, microscopic charcoal, and non-pollen palynomorph (NPP) analyses, supported by radiocarbon and radionuclide chronologies and historical aerial photograph reconstruction, are used to evaluate how Indigenous and Euro-Canadian land-use regimes are recorded in sedimentary archives and to test the extent to which recent pollen assemblages track independently documented landscape change. The long-term Bass Lake (Langman) record documents gradual Holocene forest succession punctuated by subtle late pre-contact agricultural indicators, including repeated low-abundance occurrences of Zea mays and Cucurbita-type pollen. These signals occur without sustained arboreal collapse or prolonged charcoal elevation, indicating spatially focused Indigenous land use embedded within a resilient forested landscape. In contrast, nineteenth- and early twentieth-century Euro-Canadian settlement is marked by coherent multi-proxy reorganization across sites, including increases in herbaceous and ruderal taxa, elevated disturbance indicators, and pronounced shifts in pollen assemblage structure. Independently constrained Ambrosia maxima demonstrate spatial variability in the timing and expression of agricultural expansion across the basin. North–south contrasts further indicate that closed northern basins retain clearer forested baselines, whereas hydrologically connected southern systems record persistent openness and amplified disturbance associated with agriculture, drainage, and urbanization (Chapter 2). GIS-based reconstruction of historical aerial photographs (1920s–2025) reveals divergent land-use trajectories, ranging from rapid urban expansion at Baileys Ecopark to relatively stable agricultural landscapes at Beaver River, with intermediate conditions at Bass Lake (Langman) and Rogers Reservoir. A taxon-to-land-use crosswalk linking pollen taxa to mapped land-use classes demonstrates that agricultural indicators exhibit the strongest and most consistent correspondence with reconstructed land use, while forest signals are more sensitive to fragmentation and source-area effects. Multivariate analyses show significant concordance between pollen assemblages and aerial photo-derived land-use patterns at most sites (Mantel r = 0.66–0.77; Procrustes correlation = 0.76–0.85), with reduced agreement at Bass Lake (Langman) reflecting chronological uncertainty and landscape complexity (Chapter 3). Together, these results demonstrate that Indigenous land use produced detectable but localized ecological signals, whereas Euro-Canadian land use generated broader, more persistent transformations that restructured regional ecosystems. This thesis advances a transferable framework for linking palaeoecological records with spatially explicit land-use data and provides new insight into the interpretation of ecological baselines and anthropogenic change in temperate landscapes. Keywords: palaeoecology; land-use change; Lake Simcoe watershed; pollen analysis; charcoal analysis; geospatial analysis; multi-scale analysis; Holocene reconstruction; Indigenous land-use; Euro-Canadian settlement